1992
DOI: 10.1590/s0102-76381992000200007
|View full text |Cite
|
Sign up to set email alerts
|

Modificação técnica na cirurgia da estenose aórtica supravalvar

Abstract: Rev. Bras. Cir. Cardiovasc., 7(2):121-126,1992. RESUMO : O tratamento cirúrgico convencional da estenose aórtica supravalvar caracteriza-se pela ampliação de um ou mais seios de Valsalva, utilizando-se retalhos de material protético, com ou sem secção transversal da aorta. Uma possível limitação dos resultados deste procedimento é o fato do endurecimento ou calcificação do enxerto, dificultando o desenvolvimento da raíz da aorta, mormente quando a cirurgia é realizada em criaças. Para evitar essa complicaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Sousa et al [5] have reported evolutions in 4-12 years without deaths, with residual gradients ranging from 4.5 to 26 mmHg, mild aortic insufficiency in 76.5% of patients and valve competence in 23.5%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Sousa et al [5] have reported evolutions in 4-12 years without deaths, with residual gradients ranging from 4.5 to 26 mmHg, mild aortic insufficiency in 76.5% of patients and valve competence in 23.5%.…”
Section: Discussionmentioning
confidence: 98%
“…In the distal ascending aorta, longitudinal incisions are performed in the three regions corresponding to the commissural posts of the proximal portion of the aorta. The depth of the incisions should be enough for the three protrusions may occupy the distal aortic sinus of Valsalva bottom [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A control echocardiogram showed a maximum instant gradient of 16 mmHg, compatible with the suture line. It is important to stress that there are other techniques that have excellent results without the use of prosthetic material, an extremely important fact for children and in specific situations [2,3].…”
Section: Operationmentioning
confidence: 99%
“…A control echocardiogram showed a maximum instant gradient of 16 mmHg, compatible with the suture line. It is important to stress that there are other techniques that have excellent results without the use of prosthetic material, an extremely important fact for children and in specific situations [2,3]. (Doty technique) …”
Section: Operationmentioning
confidence: 99%